SURVEY PPLP PANAHAN MANDIRI BOJONEGORO JAWA TIMUR - Slamet Raharjo (Jurnal Sport Science, 2015)
Abstract: PPLP as the center of students sport development in Indonesia needs to be monitored continuously so that the students’ achievement can be developed and maintained. The objective of the study was to monitor the archery athletes’ development in PPLP and to follow the coaching and the policy of athlete training in East Java. A survey was conducted to collect the data of athlete recruitment, human resources, identified training equipment and facilities, the methods of training, and the fund source of PPLP. The result of the study was expected to be an example of developing archery athletes in East Java. In conclusion, the development of archery athletes in Bojonegoro could be the example for others so that the archery PPLP existence can be growing better and gives precious contributions for better achievement of archery athletes in Indonesia.Key words: archery athletes, facilities, athletes, achievement.Abstrak PPLP sebagai pusat kegiatan pembinaan olahraga pelajar di tanah air perlu di-monitor secara kontinyu agar prestasi yang dicapai dapat dipertahankan dan ditingkat-kan. Tujuan penelitian untuk memonitor dan memantau pembinaan atlet PPLP panahan dan mengikuti perkembangan dan kebijakan latihan atlet di jawa timur. Metode yang digunakan survey untuk memperoleh data tentang rekruitmen calon atlet, sumber daya manusia; mengidentifikasi alat-alat dan fasilitas latihan (4) metode pelatihan yang digu-nakan, dan sumber dana penyelenggaraan PPLP. Hasil penelitian ini Recruitment Calon Atlet Panahan PPLP, Alat, Fasilitas dan Latihan di PPLP Panahan Mandiri Jawa Timur awa Timur, Sumber Daya Manusia Pembina PPLP Panahan Mandiri Jawa Timur, bisa dijadikan contoh pembinaan atlet panahan di Jawa Timur. Kesimpulan pembinaan PPLP Panahan di Bojonegoro khususnya dan Indonesia umummnya kedepan menjadi contoh, sehingga keberadaan PPLP Panahan akan semakin berkembang dan dapat mem-berikan sumbangan yang berharga bagi peningkatan prestasi panahan di Indonesia.Kata kunci: atlet panahan, manajamen, sarana dan prasarana.